Push and Pull Factors Influencing Tourist Visits to Kertalangu Cultural Village, Denpasar, Bali - Apriyani, Ni Putu Helda Silpia (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2023)
Push factors and pull factors are very important variables that motivate tourists to visit a tourist attraction. This study aims to identify the characteristics of tourists visiting the Kertalangu Cultural Village tourist attraction and examine the push factors and the pull factors that affect their visits. Data were collected by using questionnaire distributed to 180 international and domestic tourists who already visited the tourist attraction of Kertalangu Cultural Village. The collected data were then analyzed using descriptive statistical techniques and factor analysis which were processed using the SPSS 23.0 for windows program. The results showed that based on the characteristics of the respondents were mostly male, had a bachelor's education background, worked as employees, and use airplane transportation to go to Bali. The results of factor analysis identified physical factors in the recreation indicator with a loading factor value of 0.926 which is a variable that represents the push factor, which means that the factor is very strong in explaining the formed factors and the most dominant pull factor components. Factors influencing tourists were planting rice, picking vegetables, fishing, and catching ducks, in which the loading factor value was 0.932.